Investigation and simulation on transmission, emersion and dispersion of dust particle from point of generation / Mohd Syahmi Jasman - Mohd Syahmi, Jasman (2022)
Wood dust is one of the world's oldest and most prevalent occupational hazards. The current studies examine at the impact of lifetime exposure to wood dust in various occupational situations on the risk of lung cancer. In this work, the investigation on occupational safety and health in wood furniture manufacturing sectors from one factory is reported. Computational Fluid Dynamics (CFD) has now made it possible to simulate the airflow behavior using simulation applications. Knowing how the fresh air circulates within a building, around the people inside, and through its openings is crucial to improve air quality. Therefore, the purpose of this study was to use CFD to examine the air flow characteristics in a wood furniture industry. In this study, the flow was assumed to be a steady-state, incompressible, and two-dimensional turbulent flow. A standard k-epsilon turbulent model was applied to show more accurate and reasonable result. A CFD software was used to perform the numerical simulation. The simulation model of wood furniture factory was constructed with one inlet and three outlets where two opening outlets located on the top side wall while the main outlet located at the end of the factory. For the simulation model, the average air speed at the inlet was 5 m·s-1 by considering the average wind speed in our country and the speed from the fan available inside the factory. For validation of simulation model, the air quality data of particulate matter which refers to wood dust obtained from five different station are compared to the permissible exposure limit (PEL) according to the Department of Occupational Safety and Health (DOSH). The level of particulate matter pollutants are collected from several locations to identify the sources of respiratory hazards using the air quality monitor devices. The findings revealed that the sources of dangers changed depending on the workstation's purpose. Finally, two modifications are proposed on the original layout of factory to reduce the dust particle inside the factory: (1) Modification on the size of inlet and main outlet; (2) Modification on the location of inlet and main outlet. Three situations were simulated for each category of modification to predict the airflow pattern in the investigated factory. Result suggest that both inlet and outlet need to have a similar size for a smooth flow of air and the location of the outlet need to change into the middle at the end of factory in order to reduce the zero-velocity area. An addition of inlet in one of the stations are also proposed for a better result.